Proceedings of the 1st International Conference on Social, Applied Science and Technology in Home Economics (ICONHOMECS 2017) 2018
DOI: 10.2991/iconhomecs-17.2018.43
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chickpea and Okara Composite Flours on the Quality of Instant Noodles

Abstract: The study has utilized chickpea and okara composite flours and produced best formulation based on sensory and physicochemical characteristics. Formulation of F3 which comprised of 75% of wheat flour, 12.5% of chickpea flour and 12.5% of okara flour was selected as the best formulation. The qualities of best formulation and control were compared through proximate analysis, dietary fiber, energy content and cooking qualities. F3 was better than control in terms of significantly higher ash, crude protein, crude f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…The degree of volume increase during boiling of the noodles was affected by starch gelatinization and protein hydration related to the size of the starch (Kang et al, 2017). Kuen et al (2017) found the rehydration rate of noodles to range between 97.22% and 98.35%, which is slightly above the current study, while Özyurt et al (2015) reported the volume increase of noodles to be in the range of 45% to 124%, which is comparable with the results obtained in the current study of 83.53% to 100%.…”
Section: Hardness Of Noodlessupporting
confidence: 80%
See 2 more Smart Citations
“…The degree of volume increase during boiling of the noodles was affected by starch gelatinization and protein hydration related to the size of the starch (Kang et al, 2017). Kuen et al (2017) found the rehydration rate of noodles to range between 97.22% and 98.35%, which is slightly above the current study, while Özyurt et al (2015) reported the volume increase of noodles to be in the range of 45% to 124%, which is comparable with the results obtained in the current study of 83.53% to 100%.…”
Section: Hardness Of Noodlessupporting
confidence: 80%
“…The significant cooking loss obtained in F3 may have resulted from the reduced gluten strength in high RS flours. Therefore, the noodles' structure experienced disruption and weakening, which allowed the leaching of many soluble solids from the noodles into the cooking water (Espinosa-Solis et al, 2019; Kuen et al, 2017). Since the cooking losses in all four formulations were less than 12%, it was an indication that all the noodles produced were of good quality and highly accepted by consumers (Fu, 2008).…”
Section: Hardness Of Noodlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher value was found in control during storage of 90 days than standardized treatment T3. The results were in concurrence with Kuen et al [30][31][32] who shown that there was an increasing in trend of water activity from 0.243 to 0.396 in 6 months of storage in instant noodles [33][34][35][36].…”
Section: Storage Stability Studysupporting
confidence: 88%
“…The addition of CF and GBF affected the quality of macaroni products according to a nutritional point of view, decreasing carbohydrate content, but increasing RS and increasing other quality values, especially protein, fiber, and ash (Table 3). Furthermore, chickpeas are high in essential amino acids like lysine, histidine, phenylalanine, valine, and threonine (Kuen et al, 2017). Therefore, it would be the perfect dietary supplement combined with WF to improve protein quality and ensure a better overall amino acid balance.…”
Section: Effect Of Mixing Ratio Of Wf:cf:gbf On the Chemical Componen...mentioning
confidence: 99%